Dashboard Para La Visualización De Indicadores Sobre El Uso Que Tienen Los Clientes Del Aplicativo Web Sicex (2023)
The company Quintero Hermanos SAS has a valuable web application for consulting foreign trade information. Although this application records user activities in a log, the data contained therein is not used effectively to understand customers' use of the application. On the other hand, the commercial area lacks access to this information, which limits its ability to provide effective advice to clients. The problem posed focuses on how to take advantage of the historical records generated by the use of the web application to improve the advice of the commercial area to clients who carry out market research. The general objective of this project is to develop a Dashboard that displays indicators on the use of the SICEX web application, providing detailed information to the commercial team to optimize their strategies.